Spatial analysis of Prostephanus truncatus (Horn) (Coleoptera:Bostrichdae) flight activity near maize stores and in different forest types in southern Benin, West Africa - Nansen, C.; Meikle, W.G.; Korie, S. (Entomological Society of America, 2002)
Weekly Prostephanus truncatus (Horn) ßight activity, measured as the density of captured beetles in pheromone baited traps, was monitored for 76 consecutive weeks at 16 sites inside the Lama forest in southern Benin and at four sites in maize farmland just outside the forest. Prostephanus truncatus ßight activity was consistently higher and the ßight activity pattern signiÞcantly different near maize stores than at sites inside the forest. Although P. truncatus is known to infest girdled branches of Lannea nigritana (Sc. Elliot) Keay, the P. truncatus ßight activity was comparatively low at forest sites where this tree species dominated. The main peak in P. truncatus ßight activity occurred earlier in the eastern part of the forest compared with other forest parts. Ordination analysis showed that comparatively higher ßight activity in the eastern part of the forest was positively associated with the presence of teak plantations (Tectona grandis L. F.) at trap sites. The spatial distribution of weekly P. truncatus trap catches were found to be signiÞcantly aggregated during a 21-wk period, which largely coincided with the early increase in P. truncatus ßight activity in the eastern part of the forest. Based on this evidence, it was suggested that P. truncatus individuals disperse from the eastern part of the forest to other forest parts and to nearby agricultural areas, rather than, as has been previously suggested, from maize stores to the forest environment.